The Effect of Top Management Team, Firm Size and Leverage on Earnings Management with Audit Quality as A Moderation Variable - Rismawati, Rismawati; Setiany, Erna (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aims to determine the influence of the Top Management Team, Firm Size and Leverage on earnings management with Audit Quality as a Moderating Variable. This type of research is quantitative research. This study uses secondary data obtained from the Indonesian Stock Exchange (IDX) website. The sample for this research is 24 companies that have conducted an IPO for the 2017-2021 period. This study uses a purposive sampling technique as a sample selection. The analytical method of this study uses multiple linear regression analysis with Eviews 12 as an analytical tool. The result is that the top management team variable has an effect on earnings management. Firm size and leverage variables have no effect on earnings management. Audit quality moderates leverage on earnings management.